Voronovskaya Type Theorems in Weighted Spaces. (1st December 2016) - Erençin, Ayşegül; Raşa, Ioan
ABSTRACT: In this article, we introduce a generalization of Gamma operators based on a function ρ having some properties and prove quantitative Voronovskaya and quantitative Grüss type Voronovskaya theorems via weighted modulus of continuity.